The mossy fiber bouton: the "common" or the "unique" synapse? - Rollenhagen, Astrid; Lübke, Joachim H. (Frontiers in Synaptic Neuroscience, 2010)
Synapses are the key elements for signal processing and plasticity in the brain. They are composed of nearly the same structural subelements, an apposition zone including a pre- and postsynaptic density, a cleft and a pool of vesicles. It is, however, their actual composition that determines their different behavior in synaptic transmission and plasticity. Here, we describe and discuss the structural factors underlying the unique functional properties of the hippocampal mossy fiber (MF) synapse. Two membrane specializations, active zones (AZ), transmitter release sites, and puncta adherentia (PA), putative adhesion complexes were found. On average, individual boutons had ~20 AZs with a mean surface area of 0.1 µm2 and a short distance of 0.45 µm between individual AZs. Mossy fiber boutons (MFBs) and their target structures were isolated from each other by astrocytes, but fine glial processes never reached the AZs. Therefore, two structural factors are likely to promote synaptic cross-talk: the short distance and the absence of fine glial processes between individual AZs Thus, synaptic crosstalk may contribute to the high efficacy of hippocampal MF synapses. On average, an adult bouton contained ~16000 synaptic vesicles; ~600 vesicles were located within 60 nm from the AZ, ~4000 between 60 nm and 200 nm, and the remaining beyond 200 nm, suggesting large readily releasable, recycling, and reserve pools. Thus, the size of the three pools together with the number and distribution of AZs underlie the unique extent of synaptic efficacy and plasticity of the hippocampal MF synapse.